Perioperative Management of a Child with Hypoplastic Left Heart Syndrome Undergoing Cryptorchidism Surgery - Memeti, Shaban; Kuci, Saimir; Ibrahimi, Alfred; Goga, Marsela; Veshti, Altin; Buba, Sokol; Baboci, Arben (Open Access Macedonian Journal of Medical Sciences, 2022)
Hypoplastic left heart syndrome (HLHS) is a complex congenital heart condition which includes abnormal development of left sided cardiac structures leading to inadequate systemic perfusion following postnatal closure of the patent ductus arteriosus (PDA). Surgical palliation may be accomplished through a 3 staged process -Norwood procedure. This surgery is usually done within the first two weeks of your child’s life -Bidirectional Glenn procedure. This procedure is generally the second surgery. It’s done when your child is between 3 and 6 months of age. -Fontan procedure. This surgery is usually done when your child is between 18 months and 4 years of age. Patients with HLHS may need to undergo other non-cardiac surgical procedures during the first years of life posing a real challenge to the anesthesiologist, surgeon and the entire medical team. We present the case of a 18-months old, 9 kg infant who presented for cryptorchidism surgery. Cryptorchidism or undescended testis (UDT) is one of the most common pediatric disorders of the male endocrine glands and the most common genital disorder identified at birth. The main reasons for treatment of cryptorchidism include increased risks of impairment of fertility potential, testicular malignancy, torsion and/or associated inguinal hernia. The intraoperative implications of the hybrid anatomy are discussed, options for anesthetic care presented, and previous reports of anesthetic care for such patients reviewed. Conclusion: LMA combined with local anesthesia was effective to maintaining optimal cardiac function of this child patient with HLHS In summary, children with palliated HLHS have anesthetic considerations that must be followed in order to reduce perioperative morbidity and mortality in this high-risk pathology.